ADMM Strategy in Overcoming the Covid-19 Pandemic: Defense Diplomacy Perspective - Wasis Waskito; Budi Pramono; Helda Risman (Jurnal Multidisiplin Madani, 2023)
ASEAN as a regional organization is considered slow and less unified in tackling the Covid-19 pandemic. In the midst of these problems, ADMM as the main defense cooperation organization was more agile in responding to the pandemic that had begun to spread. This study aims to analyze ADMM's strategy in overcoming the Covid-19 pandemic from the perspective of defense diplomacy. The research uses a quasi-qualitative approach with interactive model analysis technique and with data obtained from literature study technique. The findings show that ADMM has carried out securitization of Covid-19, which has had an impact on the formation of regional perceptions regarding the threat of a pandemic that attacks common interests. To overcome the pandemic, ADMM has deployed defense cooperation in the fields of military medicine and CBR. In the midst of space and time constraints, ADMM was forced to modify their defense diplomacy strategy into virtual defense diplomacy. This model of defense diplomacy is an important lesson for ASEAN's defense diplomacy activities to face the same threat in the future